Monocentric retrospective clinical outcome in a group of 13 patients with opsoclonus myoclonus syndrome, proposal of diagnostic algorithm and review of the literature - Urtiaga Valle, Sarai; Souvannanorath, Sarah; Leboucq, Nicolas; Haouy, Stephanie; Rivier, François; Roubertie, Agathe; Meyer, Pierre (European journal of paediatric neurology, 2022)
Dancing eye syndrome or opsoclonus-myoclonus syndrome (OMS) is a very rare disease (incidence <1/5,000,000 per year), which is more prevalent in young children. Although it is not usually a cause of mortality, the aftermaths are not rare. We performed an observational retrospective review of children diagnosed with OMS in our neuropediatric department from 1996 to 2020, with the objective of assessing the prognostic value of initial clinical features. All medical data from diagnosis to last follow-up were reviewed. We defined unfavorable evolution of OMS as persistence or worsening of symptoms. Subsequently, based on a literature review, our results and experience, a diagnostic algorithm was developed. A total of 13 OMS patients were included: 61.5% were male (n = 8), median age at diagnosis was 18 months (IR = 76), median treatment delay was 14 days (IR = 146) and OMS score at onset was 8 (IR = 11). The most frequent etiologies were neuroblastoma-associated and idiopathic OMS (38.46%; n = 5) of the patients, followed by post-infectious OMS (n = 3). All the patients were treated with corticosteroids, five required a surgical intervention (neuroblastoma group), and three required adjunctive immune therapy (immunoglobulins, cyclophosphamide and/or rituximab). We detected neurodevelopmental disorders in 38.46% (n = 5) of the patients, mainly attention deficit (n = 4), and persistent sleep disturbances (n = 4). The median OMS score at the end of follow-up was 1 (IR = 3). An important diagnostic delay, OMS score of ≥10 and age >1 year at onset may correlate with a higher risk of aftermaths. We detected a better prognosis in the post-infectious OMS, with full recovery occurring in 2/3 of patients. Early clinical suspicion is key to guarantee maximum response of treatment.